Democratic Republic of the Congo : 2012 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Democratic Republic of the Congo. (IMF Staff Country Reports; Country Report ;, 2013)
Economic performance in the Democratic Republic of the Congo (DRC) has improved markedly. To safeguard the fiscal position, the government has to rigorously monitor budget execution and reduce nondiscretionary spending. The current monetary and floating exchange rate regime should be maintained. Recent efforts to shore up financial stability and develop the banking sector give opportunities for closer regional and global financial integration. Institutional weaknesses, the business environment, and establishing a strong foundation for the exploitation and development of DRC's natural resources will be critical.